The Importance of Agriculture and Tree Plantation in the Light of Sirat-un-Nabi (SAW): کاشت کاری اور شجرکاری کی اہمیت سیرت النبی ﷺکی روشنی میں - Akhtar, Dr. Nisar; Shah, Dr. Noor Wali; Nawaz, Haq (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
This article explores the significance of cultivation and tree plantation in the light of the Seerah of the Prophet Muhammad ﷺ. In a time when environmental degradation poses a serious threat to global ecosystems, Islamic teachings offer profound guidance rooted in divine revelation. Drawing from the Qur’an and authentic Hadiths, the study illustrates how the Prophet ﷺ not only encouraged agriculture and afforestation but also actively practiced and promoted them as acts of virtue and sadaqah jariyah (ongoing charity). The Qur’anic verses emphasize the role of greenery and plantations as manifestations of divine power and as a source of sustenance and ecological balance. The Prophet’s sayings commend farmers and those who plant trees, promising eternal reward for any benefit derived from their efforts—even by animals or strangers. The article also highlights the practices of the Prophet’s Companions, including their environmental ethics and emphasis on land rehabilitation and sustainable agriculture. Notably, the study underlines how the Islamic worldview sees tree planting as an act of worship that benefits the environment, economy, and future generations. This synthesis of Islamic guidance with contemporary environmental concerns provides a framework for responsible ecological stewardship rooted in spiritual values. The findings of this study affirm that tree plantation is not only a moral and ecological necessity but also a religious obligation in the Islamic tradition۔